A note on immersion intertwines of infinite graphs. Issue 1 (12th December 2018) - Barnes, Matthew; Oporowski, Bogdan
Abstract: We present a construction of two infinite graphs G 1 and G 2, and of an infinite set F of graphs such that F is an antichain with respect to the immersion relation and, for each graph G in F, both G 1 and G 2 are subgraphs of G, but no graph properly immersed in G admits an immersion of G 1 and of G 2 . This shows that the class of infinite graphs ordered by the immersion relation does not have the finite intertwine property.